Determination of suitable microspore stage and callus induction from anthers of Kenaf (Hibiscus Cannabinus l.) - Ahmed Mahmood Ibrahim; Fatimah Binti Kayat; Zeti Ermiena Surya Mat Hussin; Dwi Susanto; Mohammed Ariffulah (2014)
Kenaf (Hibiscus cannabinus L.) is one of the important species of Hibiscus cultivated for fiber. Availability of homozygous parent lines is prerequisite to the use of the heterosis effect reproducible in hybrid breeding. The production of haploid plants by anther culture followed by chromosome doubling can be achieved in short period compared with inbred lines by conventional method that requires self pollination of parent material. In this research, the effects of the microspore developmental stage, time of flower collection, various pretreatments, different combinations of hormones, and culture condition on anther culture of KB6 variety of Kenaf were studied. Young flower buds with immature anthers at the appropriate stage of microspore development were sterilized and the anthers were carefully dissected from the flower buds and subjected to various pretreatments and different combinations of hormones like NAA, 2,4-D, Kinetin, BAP, and TDZ to induce callus. The best microspore development stage of the flower buds was about 6–8 mm long collected 1-2 weeks after flower initiation. At that stage, the microspores were at the uninucleate stage which was suitable for culture. The best callus induction frequency was 90% in the optimized semisolid MS medium fortified with 3.0 mg/L BAP + 3.0 mg/L NAA.